GIJZELING DALAM TEORI DAN PRAKTEK ACARA PERDATA DI INDONESIA - Gandes Candra Kirana (Jurnal Hukum PRIORIS, 2021)
The definition of gijzeling according to Article 1 of PERMA No. 1 of 2000 that gijzeling is defined by the term "Forced Agency", namely an indirect forceful attempt to enter a debtor with bad intentions into a State Detention Center determined by the Court, to force the person concerned to fulfill his obligations; A debtor with bad faith is a debtor, guarantor or guarantor of debt who is able but does not want to fulfill his obligations to pay his debts; Agency coercion cannot be imposed on debtors with bad faith who have reached the age of 75; and Corporate Coercion can only be imposed on debtors with bad faith who have debts of at least Rp. 1,000,000,000 (one billion rupiah). The legal basis for Gijzeling is Article 209 HIR and Article 242 RBg, which were later revoked by SEMA No. 2 in 1964, and was reinstated with PERMA No.1 in 2000. The type of research used is Normative where the researcher tries to carry out legal synchronization research on secondary data contained in statutory regulations and books and scientific writings of legal experts. This research is descriptive in nature, namely research in which knowledge or theories about the object to be studied already exist and want to provide an overview of the object of research; while the data sources used are secondary data sources which include primary and secondary legal materials. Gijzeling arrangements in Civil Procedure Law are only regulated by PERMA No.1 of 2000 concerning Forced Institutions in which there are still many weaknesses, especially regarding regulations regarding the Implementation of Gijzeling itself and the regulation must be by law so that the implementation of Gijzeling can be carried out effectively. Keywords: Gjzeling; Civil Procedure Law